Les nourritures terrestres dans l’œuvre d’Athina Papadaki - Sophie Coavoux (Cahiers Balkaniques)
Subject of extremely varied treatments, food is of central importance in the work of Athina Papadaki and it holds different metaphorical meanings. Analyzing the theme of food throughout the work, with a special focus on the collection Food leaves, allows one to follow the whole creative itinerary of this gastrosoph poet.